Early Detection and Control of Hypertention through the CERDIK Approach in Adult Patients at Lempake Public Health Center: Deteksi Dini dan Pengendalian Penyakit Hipertensi dengan CERDIK Pada Pasien Dewasa di Puskesmas Lempake - Fadhilah, Nurul; Nurandini, Anisa Dwi; Mananna', Esran; Wijaya, Viriyanata (ANDIL Mulawarman Journal of Community Engagement, 2026)
Hypertension is one of the major public health problems with an increasing prevalence and is a significant risk factor for cardiovascular diseases. Health promotion efforts through early detection and control of hypertension using the CERDIK approach (Regular health check-ups, Eliminate cigarette smoke, Exercise regularly, Adopt a healthy and balanced diet, Get adequate rest, and Manage stress) are crucial. This activity aimed to provide information related to early detection of hypertension to adult patients at Lempake Primary Health Center, deliver CERDIK education to adult patients, and encourage them to adopt a healthy lifestyle and monitor their blood pressure independently and regularly. The health promotion program was carried out through counseling, blood pressure measurement, and healthy exercise sessions. The results showed that this program was effective in improving knowledge, awareness, and interest of the community in conducting early detection of hypertension and adopting CERDIK-based healthy behaviors. Therefore, health promotion using the CERDIK approach can serve as a sustainable preventive and promotive strategy for hypertension control in the community.